The remaking of local government in the Eastern Cape: economic, demographic and political challenges - Wood, Geoffrey (University of the Free State, 2000)
This paper focuses on the problems and prospects of urban local government in the Eastern Cape region of South Africa. It commences with an overview of the institutional framework of local government in South Africa. Secondly, it assesses the 1995 local government elections in the province, and the nature and extent of party political competirion at the local level. Thirdly, likely demographic trends are reviewed, along with their implications in terms of service provision. This is followed by a consideration of the revenue and planning crises confronting local authorities in the region. This issue is located within the context of specific patterns of urbanisation and economic readjustment. It is concluded that, while the detacialisation of local government represents a significant extension of South Africa's new democracy, fiscal, demographic and political realities militate against any meaningful and sustainable devolution of power over the medium and long term.

Hierdie artikel fokus op die probleme en vooruitsigte van plaaslike bestuur in die Oos-Kaapstreek van Suid-Afrika. Daar word begin met 'n oorsig van die institusionele raamwerk van plaaslike bestuur. Tweedens word die 1995-verkiesing van die plaaslike bestuur in die streek beoordeel, en die aard en omvang van partypolitieke wedywering bespreek. Derdens word waarskynlike demografiese onrwikkelinge bespreek en die implikasies daarvan vir diensverskaffing. Vervolgens word aandag gegee aan belasting en beplannning in die streek. Die hele kwessie word geplaas binne die raamwerk van die patrone wat verstedeliking en ekonomiese aanpassing vertoon. Die gevolgtrekking word gemaak dat alhoewel die nie-rassigheid van plaaslike besture 'n belangrike stap voorwaarts in Suid-Afrika se demografiese ontwikkeling is, daar fiskale, demografiese en politieke realiteite is wat volhoubare ontwikkeling oor die medium en lang termyn sterk teenspreek.
Keywords: Local government; Eastern Cape; Democracy; Urban local government; Local government elections